Mesona chinensis Benth polysaccharides alleviates liver injury by beneficial regulation of gut microbiota in cyclophosphamide-induced mice - Yuzhen Hong; Mingyue Shen; Lixin Huang; Ting Wu; Jianhua Xie (Food Science and Human Wellness)
There are a number of health benefits of Mesona chinensis Benth polysaccharide (MP), but little is known about its hepatoprotective effect and effect on gut microbiota composition in mice with liver damage induced by cyclophosphamide (CTX). This study indicated that MP supplementation effectively inhibited the production of serum aspartate aminotransferase (AST) and alanine aminotransferase (ALT), enhanced liver antioxidant capacity and repaired liver damage in mice caused by CTX. The release of inflammatory cytokines in liver and the concentration of lipopolysaccharide (LPS) in serum were decreased, and the level of short chain fatty acids (SCFAs) in colon was increased after MP administration. Those effects may be correlated with the regulation of the gut microbiota. Importantly, MP restrained liver inflammatory responses induced by CTX may via increasing the SCFAs-producing bacteria family Ruminococcaceae and reduced LPS-producing bacteria genus Bacteroides. In short, the prevention of CTX-induced liver injury by supplementing MP is achieved at least in part by regulating the community structure of the gut microbiota, and MP is expected to be a potential prebiotic to treat and prevent liver diseases.